Adoption of recommended dairy farming practices by farmers in Maharashtra under Kamdhenu Dattak Gram Yojana - Kad, Sanjay Vasant; Kadian, KS; R, Raju; Kad, Suresh (Indian Journal of Dairy Science, 2020)
The present study aimed to measure the extent of adoption of recommended dairy farming practices by farmers of Pune and Nashik divisions of Maharashtra which were selected based on livestock population and milk production in the year 2018-19. From each division two districts were selected randomly and from each district two blocks were selected randomly. From each block one adopted and one non-adopted village under the Kamdhenu Dattak Gram Yojana scheme were selected From each village 15 dairy farmers were selected on random basis. Overall, 240 dairy farmers were selected, as the respondents for this study constituting 120 beneficiaries farmers and 120 non-beneficiaries of the Kamdhenu Dattak Gram Yojana. The quantitative and qualitative data were collected through interview schedule, discussion, observation and available secondary sources. Findings indicated that the most of beneficiaries (43.33%) were in medium level overall adoption and majority of non-beneficiaries (62.50%) had fallen in low level of overall adoption category on recommended dairy farming practices covering breeding, feeding, health, general management and waste management practices. The overall adoption index of recommended dairy farming practices of beneficiaries (75.31) was found to be more compared to non-beneficiaries (66.75) of the scheme found highly significant at 5 per cent level of probability using ‘Z’ test. Based on adoption index, maximum adoption of dairy farming practices was found in case of Breeding practices, whereas minimum adoption was found in case of Waste management practices in both beneficiaries and non-beneficiaries of the scheme. The results clearly indicated that the Kamdhenu Dattak Gram Yojana had created positive impact on the adoption level of the beneficiaries of scheme by adopting higher recommended dairy farming practices compared to the non-beneficiaries of the scheme.